Subsurface Investigation of Tuba Oil Field Depending on 2D Seismic Reflection South Iraq - Z. Khorshd , Salman; Almarsoomy, Dlal F. (Iraqi Journal of Science, 2023)
This study deals with the seismic reflection interpretation of Cretaceous Formations in Tuba oil field, southern Iraq, including structural and stratigraphic techniques. The study achieved by using Geofram , Geolog and Petrel software. The interpretation process, of 2-D seismic data and well logs have been used. Based on well logs and synthetic traces two horizons were identified and picked which are the tops of Mishrif and Zubair Formations. These horizons were followed over all the area in order to obtain their structural setting. Structural interpretation indicates that the Tuba oil field is an anticline structure as well as the presence of normal fault near Mishrif Formation trending NE-SW. Information from the wells appeared Mishrif Formation deposited on shelf areas with no basinal sites, the nature of the Mishrif Formation in the study area deposits (MB1, MB2and MA) represents the highstand system tract (HST) shallow facies deposited in high-energy. Amplitude geometry of reflections within the reservoir units for Mishrif and Zubair Formations are moderate to high amplitude which is the presence of lateral variations in the geologic facies. Reflection continuity in Mishrif Formation (SF1) and (SF2) between parallel to subparallel which indicates some uniform in sediment, divergent reflection configuration (SF3) is found in Zubair Formation that indicates wedge shaped also, subparallel reflection configuration (SF4) in Zubair Formation has relatively uniform strata where delta depositions. Stratigraphic interpretation of seismic facies indicated that the Mishrif Formation represents progradational seismic facies (mounded), uniformity Mishrif indicated deposit in stable environment while Zubair Formation represents aggredation and progrodation seismic facies (shingled) that was deposited in delta environment.